Upaya Mengembangkan Motorik Kasar Anak Melalui Menari Pada Kelompok B2 Di TK Al Islam I Jamsaren Surakarta Tahun Pelajaran 2014/ 2015 - FITRIANA, FITRIANA; , Dra. Surtikanti, M.Pd (2015)
Dancing is one of the activities that appeal to children and children can develop gross motor skills in a fun way. The fact was that the low gross motor skills of the child due to the teacher's activity less attractive, and more fine motor activities conducted. In addition, the classrooms were less conducive to physical activity. This study aimed to determine the development of gross motor skills through dancing in kindergarten Al Islam I Jamsaren Surakarta group B2. This research was carried out with the number of 31 children. This type of research was classroom action research (PTK), the method of data collection was using observation, interview, and dokumentation methods. Observation was used to collect data gross motor development of children. Interviews was conducted with the teacher on classB2. It was done in order to know the learning process on developing the gross motor skills on the student of Al Islam I Jamsaren Surakarta. Documentation is a set of record about events that happened in the pas or recently occurred. Based on calculations of each cycle of gross motor development the kindergarten result in precycle was 31.8%, then on the first cycle was obtained 52.3%, 74.2% earned second cycle and third cycle gained 86.2%. Therefore efforts to develop gross motor skills of kindergarten children Al Islam I Jamsaren Surakarta B2 group was successful because it had met the predetermined maximum was 80%. Keywords: Gross motor, Dancing Event